COMPARATIVE STUDY OF THE EFFECT OF REGENERATION STIMULATION DRUG ON THE STRUCTURE AND RATE OF HAIR GROWTH IN WHITE RATS - Olga B. Zhdanova; Iraida I. Okulova; Elena B. Dunaeva; Olga V. Chasovskikh (Siberian Journal of Life Sciences and Agriculture)
Background. The study of the activation process of hair papilla stem cells when using regeneration stimulators to improve the structure of the hair and its growth rate is relevant both for the development of drugs for fur farming and alopecia treatment regimens. In this study, an attempt was made to stimulate stem cells in the hair papilla and improve the quality of hair.